Redefining value: a discourse analysis on value-based health care - Gijs Steinmann; Hester van de Bovenkamp; Antoinette de Bont; Diana Delnoij (BMC Health Services Research, 2020)
Abstract Background Today’s remarkable popularity of value-based health care (VBHC) is accompanied by considerable ambiguity concerning the very meaning of the concept. This is evident within academic publications, and mirrored in fragmented and diversified implementation efforts, both within and across countries. Method This article builds on discourse analysis in order to map the ambiguity surrounding VBHC. We conducted a document analysis of publicly accessible, official publications (n = 22) by actors and organizations that monitor and influence the quality of care in the Netherlands. Additionally, between March and July 2019, we conducted a series of semi-structured interviews (n = 23) with national stakeholders. Results Our research revealed four discourses, each with their own perception regarding the main purpose of VBHC. Firstly, we identified a Patient Empowerment discourse in which VBHC is a framework for strengthening the position of patients regarding their medical decisions. Secondly, in the Governance discourse, VBHC is a toolkit to incentivize providers. Thirdly, within the Professionalism discourse, VBHC is a methodology for healthcare delivery. Fourthly, in the Critique discourse, VBHC is rebuked as a dogma of manufacturability. We also show, however, that these diverging lines of reasoning find common ground: they perceive shared decision-making to be a key component of VBHC. Strikingly, this common perception contrasts with the pioneering literature on VBHC. Conclusions The four discourses will profoundly shape the diverse manners in which VBHC moves from an abstract concept to the practical provision and administration of health care. Moreover, our study reveals that VBHC’s conceptual ambiguity largely arises from differing and often deeply rooted presuppositions, which underlie these discourses, and which frame different perceptions on value in health care. The meaning of VBHC – including its perceived implications for action – thus depends greatly on the frame of reference an actor or organization brings to bear as they aim for more value for patients. Recognizing this is a vital concern when studying, implementing and evaluating VBHC.